Cover Picture: Encapsulation of Perovskite Solar Cells for High Humidity Conditions (ChemSusChem 18/2016). Issue 18 (13th September 2016) - Dong, Qi; Liu, Fangzhou; Wong, Man Kwong; Tam, Ho Won; Djurišić, Aleksandra B.; Ng, Annie; Surya, Charles; Chan, Wai Kin; Ng, Alan Man Ching
Abstract : The Cover picture shows the outdoor testing performance of perovskite solar cells in a hot and humid environment (Hong Kong summer). Different encapsulation techniques are examined for perovskite solar cells. The cells encapsulated with a SiO2 thin film and cover glass packaging incorporating desiccant and UV‐curable epoxy exhibit good performance in accelerated lab testing under illumination and at 85 °C, as well as in outdoor testing in Hong Kong. More details can be found in the Full Paper by Dong et al. onpage 2597 in Issue 18, 2016 (DOI:10.1002/cssc.201600868 ).